A Philosophical Critique of Empirical Arguments for Postmortem Survival by Michael Sudduth - Jenkins, Hannah (Journal of Scientific Exploration, 2016)
A Philosophical Critique of Empirical Arguments for Postmortem Survival doesn’t have the snappy title of Stephen E. Braude’s Immortal Remains, but it does do exactly what it says on the cover with a similar level of sophisticated analysis and thorough understanding of both the evidence and the arguments for survival after death. The book commences with a summary of the types of evidence and stances taken regarding the evidence and the possibility that humans somehow survive after death. He hones the evidence down to three kinds of phenomena: out of body and near death experiences, mediumistic communications, and cases of the reincarnation type (p. 3). He displays a thorough command of the historical and contemporary literature with his summary of the major contributors to the survivalist debate from both the empirical and philosophical examinations before staking out the territory he will focus on in the book: the classical empirical arguments for survival. Sudduth presents the bones of the explanatory survival argument as follows: 1) There is some body of empirical facts F. 2) The hypothesis of personal survival S explains F. 3) No other hypothesis C explains F as well as S does. Therefore: 4) S is the best explanation of F (p. 9).